Improving the Knowledge of Mothers of Toddlers and Preschool Children on Early Detection of Child Growth and Development through the Prona-Kepo Approach - Mariyani Mariyani; Ita Herawati; Resi Galaupa (Postgraduate, University of Mataram, 2025)
Hypertension PRONA-KEPO as a solution with an educational and participatory approach. This program integrates the role of Family Development for Toddlers and Preschool Children, which focuses on strengthening family knowledge and integrated health posts that provide basic health services and monitoring of child development to reduce the incidence of stunting. The study used a quasi-experimental design with a non-equivalent control group design. The sample determination used purposive sampling. The results showed that there was a change in knowledge before and after the intervention in the intervention and control groups. In the intervention group, the mean value before the provision of health literacy in the form of augmented reality was 60.8 ± 1.06 and experienced an increase in the mean value to 92.3 ± 0.86, while in the control group, the previous 57.9 ± 0.87 experienced a smaller increase to 80.5 ± 1.04. The results of the Wilcoxon test in the intervention group obtained a p-value = 0.012 < α = 0.05. Meanwhile, in the control group, the p-value obtained was 0.005 > α = 0.05.